LEGAL AND ETHICAL-NORMAL RELATIONS, CULTURE OF MUTUAL COMMUNICATION IN THE ARMED FORCES OF THE REPUBLIC OF UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
My article entitled "Legal and ethical-normative relations, culture of mutual communication in the Armed Forces of the Republic of Uzbekistan" is very important current information on educating the young generation studying in educational institutions in the spirit of spirituality, ethics and patriotism. serves as.